2006
DOI: 10.1521/aeap.2006.18.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Lack of HIV Testing and Awareness of HIV Infection Among Men Who Have Sex With Men, Beijing, China

Abstract: In China, men who have sex with men (MSM) are at high risk for HIV. However, little is known about their HIV testing behavior. From September 2001 to January 2002, we recruited 482 men through social networks and MSM venues. We conducted HIV testing and counseling, and anonymous, standardized face-to-face interviews. Eighty-two percent of participants had never tested for HIV before the study. The most common reasons for not testing were perceived low risk of HIV infection (72%), not knowing the location of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
83
5
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 23 publications
10
83
5
1
Order By: Relevance
“…The differences between Zambian youths and Ethiopian military personnel may be affected by the different occupational contexts. However, these results fell in line with a study done on a Chinese population which found that consistent condom use tended to increase with educational level (Choi, et al, 2006). It is also possible that the more educated youth were better informed about the possible risks of not using a condom.…”
Section: Discussionsupporting
confidence: 86%
“…The differences between Zambian youths and Ethiopian military personnel may be affected by the different occupational contexts. However, these results fell in line with a study done on a Chinese population which found that consistent condom use tended to increase with educational level (Choi, et al, 2006). It is also possible that the more educated youth were better informed about the possible risks of not using a condom.…”
Section: Discussionsupporting
confidence: 86%
“…Such a trend could be under way in several cities. In Beijing, HIV prevalence of 3% and 4.6%, respectively, has been found in two studies among men who have sex with men (Choi KH et al, 2006;Ma et al, 2006). One in five of the men participating in the latter study (in 2005) had never heard of HIV, and more than two in three reported unprotected sex in the previous six months .…”
Section: Migration and Hiv Risk In Chinamentioning
confidence: 99%
“…The results of some studies indicated that fear can influence the access to treatment and care services and it has been seen as a barrier to help seeking (23,24). They state that their reluctance to AIDS services is a strategy for protection of the patient and the family from stigma and social isolation (23,25).…”
Section: Introductionmentioning
confidence: 99%